Pious citizens: reforming Zoroastrianism in India and Iran - Ringer, Monica M. (Modern intellectual and political history of the Middle East, 2011)
Introduction: modernity, religion, and the production of knowledge -- Bombay and murmurs of reform: religion as "civilization" and "progress" -- The Protestant challenge to Zoroastrianism -- The Parsi response: rational religion and the rethinking of tradition -- Western religious studies scholarship: historicism and evolutionism -- Parsi religious reform in the second generation: the recovery of "true" religion -- The Parsi rediscovery of ancient Iran -- Iranian nationalism and the Zoroastrian past -- Kay Khosrow Shahrokh: rational religion and citizenship in Iran -- Conclusion: religion and the creation of pious citizens